Low-Dimensional and Nanostructured Materials and Devices Properties, Synthesis, Characterization, Modelling and Applications - Ünlü, Hilmi; Horing, Norman J. M.; Dabrowski, Jaroslaw; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on the fundamental phenomena at nanoscale. It covers synthesis, properties, characterization and computer modelling of nanomaterials, nanotechnologies, bionanotechnology, involving nanodevices. Further topics are imaging, measuring, modeling and manipulating of low dimensional matter at nanoscale. The topics covered in the book are of vital importance in a wide range of modern and emerging technologies employed or to be employed in most industries, communication, healthcare, energy, conservation , biology, medical science, food, environment, and education, and consequently have great impact on our society.  .
Modelling of Electronic Properties of Low Dimensional Semiconductors -- CdSe-Based Quantum Dots, Synthesis, Characterisation and Modelling -- Growth and Characterisation of CdTe Quantum Dots -- Nanostructured Materials for Solar Cells -- Metal Organic Chemical Vapor Deposition (Growth) of GaN Low-Dimensional Structures -- Low-Dimensional GaN Structures, Characterization and Fabrication -- Pulsed Laser-Assisted Formation of Semiconductor Nanoparticles -- Computational Studies of Doped ZnO Nanowires -- Computing with Emerging Nanotechnologies -- Nanomagnetism and Spintronics -- Growth and Porperties on InN -- Structural, Optical and Electrical Properties of Tungsten Oxide-Based Thin Films and Nanofibers -- Solvent and Potential Effect of Electropolymerized 3,4 Thiophene on Electrochemical Impedance Behaviour -- The Challenge to Develop Nanometrology: Microscopy and Modelling as Parallel Approaches -- Semiconducting Carbon Nanotubes: Properties, Characterization and Applications -- Effects of Charging and Perpendicular Electric Field on Graphene Oxide -- Bionanotechnology: Lessons from Nature for Better Material Properties -- Nanotechnology Applications in Modern Medicine -- Microfluidics and its Applications in Bionanotechnology -- Quantum Dots in Bionanotechnology and Medical Science -- Synthesis and Biological Applications of Quantum Dots.
Keywords: Nanoscience; Optical materials; Microtechnology; Microelectromechanical systems; Nanochemistry; Nanophysics; Optical Materials; Microsystems and MEMS; Nanochemistry